Art Music by Caribbean Composers: Introduction to Volume 2 - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2013)
The second volume of the Caribbean Art Music Bibliography will include many of the Caribbean countries with a strong art music tradition: Trinidad and Tobago, Dominica, Aruba, Bonaire, Curacao, Barbados, and Martinique.